Could a new record change the range of distribution of a little - known bat species (Vespertilionidae: Eptesicus innoxius)? - Loaiza S., Christian R.; Salas, Jaime A.; Au Hing, Andrea (THERYA, 2019)
We report the first record of Eptesicus innoxius in northwestern Ecuador, in the province of Esmeraldas, occurring in a disturbed area, at 134.3 km northwest from the nearest known locality in Ecuador, which represents an important latitudinal extension in the distribution of this species. A predictive distribution model is presented using a total of 43 records from localities of Ecuador and Perú, and its distribution area is determined by a minimum convex polygon (PMC). The sensitivity value obtained in the test data was 0.984 and the area under curve ROC (AUC) value obtained (0.979) indicates an acceptable confidence level. Based on new records and known records, we estimate its distribution area in 135,243 km2. The environmental variables with the greatest influence in the distribution of E. innoxius were: Precipitation seasonality (37.4 %), Minimum temperature of coldest month (20.1 %), Precipitation of driest month (14.5 %), and Mean temperature of wettest quarter (12.8 %). This data show that E. innoxius has been recorded mainly in tropical dry forest, but also has presence in humid areas. Within these new reports, we recommended an upgrade of its conservation status in Ecuador and Perú.